THE BIOGRAPHY OF PUANG MASSER AND HIS PAPERS - Idham Idham (Al-Qalam, 2020)
Since long time ago, Indonesia contributes to one of the largest Muslim scholar graduates in the world, these scholars are not only recognized in their countries, but are recognized throughout the world. They are Nuruddin Ar Raniri (Aceh), Sheikh Nawawi al Bantani (Banten), Khalil Bangkalan (Madura), Sheikh Muhammad Arsyad al Banjari (South Kalimantan), Sheikh Yusuf al Makassari (South Sulawesi), Sheikh Ahmad Khatib al Minangkabawi and Muhammad Jamil Jambek (West Sumatra), Sheikh Mahfudz Tremas (Java), following Hadhratus Sheikh KH. Hasyim Asy'ari (founder of  Nahdatul  Ulama),  KH. Ahmad  Dahlan (founder of  Muhammadiyah),  Prof.  Dr.  Hasbi  ash- Shidiqqey (initiator of Indonesian jurisprudence), Prof. Buya Hamka, and so on. The number of scholars in Indonesia will never be exhausted to be studied, because scholars always grow and develop in the community. Some of the scholars have written their biographies, but many of them have not yet been written. The absence of written sources (reading) about the scholar makes the public not familiar with it. So the purpose of writing this short biography is to find out a short biography of one of the scholars, namely Dr. Muhammad Nawawi Yahya Abudrrazak Al Majene, from Mandar, West Sulawesi. Nawawi Yahya is known by the local people by the name of Puang Masser, because most of his life was spent in Egypt in the context of studying. From the undergraduate program until the doctoral program was completed in Egypt. Nawawi Yahya or Puang Masser managed to write a dissertation entitled "Az Zakah wa an Nadzum al Ijtima'iyah al Mu'ashirah", Zakat  and  the  Order of the  Contemporary Society. What's interesting  about the dissertation is its thickness reaches 3,593 pages, which is divided into six chapters. The work has now been published by the Research Center for Literature and the Religious Khazanah of the Indonesian Ministry of Religion's Research and Development Agency. This study used interviews, observations, and documentation in collecting data as well as qualitative research in general.